The Role of Counseling in the Peumulia Jamee Tradition in Acehnese Society - Zahra Nelissa; Agus Taufiq; Noor Anidaisma Binti Ahmad Yusuf; Khairiah, Khairiah (Perkumpulan Cendekia Muda Kreatif Indonesia, 2026)
Effective counseling is highly dependent on the counselor's ability to build a strong and culturally relevant relationship with the client from the outset. This study aims to explore the relationship between the values of the Peumulia Jamee tradition in Acehnese society and culturally grounded counseling practices. A Systematic Literature Review (SLR) method was used, involving searches across databases such as Google Scholar, ResearchGate, and national and international repositories, using keywords such as “Peumulia Jamee,” “counseling,” and “local wisdom.” From a total of 260 articles identified, 210 were screened after duplicates were removed, and 20 were included in the final synthesis based on inclusion criteria. The findings reveal that values embedded in Peumulia Jamee—such as respect, hospitality, openness, and care—are aligned with core principles of humanistic counseling and strengthen counselor-client relationships. The integration of these cultural values enhances comfort, trust, and the overall effectiveness of the counseling process, particularly within the Acehnese context. It can be concluded that Peumulia Jamee offers a culturally relevant foundation for developing more empathetic, contextual, and effective indigenous counseling approaches.